Wawasan Metode Kajian Islam - Muhammad Taufiqurrahman; Giant Adi Sasongko; Eko Nursalim (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This article explores the methods and scientific paradigms in Islamic studies using a library research approach through a review of recent literature published after 2020. The findings indicate that Islamic studies have shifted from a purely textual-normative orientation to multidisciplinary and interdisciplinary approaches that incorporate bayani, burhani, and irfani perspectives, as well as historical, philosophical, and sociological analyses. The scientific paradigms in Islamic studies can be categorized into four main models: normative-theological, historical-sociological, philosophical-rational, and integrative-interdisciplinary. Therefore, Islamic studies should ideally be inclusive, adaptive, and dialogical—preserving the authority of revelation while remaining relevant to social dynamics and the advancement of knowledge